KADAR AIR DAN BILANGAN ASAM DARI MINYAK KELAPA YANG DIBUAT DENGAN CARA TRADISIONAL DAN FERMENTASI - N. G. A. M. Dwi Adhi Suastuti (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2009)
The water contents and acid numbers of coconut oils made by thad way and by fermentation werecompared. The water contents were determined using oven method while the acid numbers was cletermined bytitration. Both parameters were compared on oils exposed to open air for 0, 1, 2, 3, and 4 weeks.Result showed that water contents and acid value of coconut oils produced by fermentation process werehigher than coconut oils made by traditional ways. Water content of coconut oil made by traditional way and byfermentation were elevated during exposure. The highest water content of both coconut oils made by traditional wayand fermentation process after 4 weeks exposure were 0,03 % and 0,06 % respectively, while the highest acidnumbers of both coconut oils products after 4 weeks exposure were 0,75 and 0,89 mg KOH/g respectively